A patient with hepatocellular carcinoma who developed invasive pulmonary aspergillosis after corticosteroid treatment. Issue 8 (10th August 2021) - Sato, Shintaro; Yamada, Sho; Nishizawa, Tomotaka; Oba, Tomohiro; Kawabe, Rie; Yamakawa, Hideaki; Akasaka, Keiichi; Amano, Masako; Matsushima, Hidekazu
Abstract: Lung or head and neck cancer have been indicated as solid cancers associated with invasive pulmonary aspergillosis (IPA), but the relationship with hepatocellular carcinoma (HCC) is unknown. We report a case of HCC in which the presence of cirrhosis and corticosteroid administration may have caused the development of IPA. Abstract : The presence of hepatocellular carcinoma, cirrhosis of the liver, and corticosteroid administration predisposed the patient to the development of invasive pulmonary aspergillosis.